Immune checkpoint inhibitors in therapy of non-small cell lung cancer (a review) - Kolesnik, O. P.; Mykhailychenko, V. V. (Zaporozhye Medical Journal, 2021)
Aim. Based on scientific literature data, to evaluate the effectiveness of the use of immune checkpoint inhibitors (ICI) in the treatment of non-small cell lung cancer (NSCLC). Materials and methods. To analyze the results of clinical trials of NSCLC treatment with immune checkpoint inhibitors. Conclusions. Among the immune checkpoint inhibitors, PD-1/PD-L1 inhibitors, namely Nivolumab, Pembrolizumab and Atezolizumab, are most successful in the treatment of NSCLC. Their use significantly increases overall survival and progression-free survival with a lower profile of adverse events. They are prescribed as both second-line and first-line drugs in the NSCLC therapy. Such biomarkers as Teff gene expression level, tumor mutational load (TMB) level and interferon gamma (IFNG) mRNA expression level have also been identified. They allow to more accurately determine the group of patients who will show the best response to therapy with PD-1/ PD-L1 inhibitors.